Розрахункова модель випаровувань автозаправних станцій - Івасенко, В. М. (НТУ "ХПІ", 2014)
Проаналізовано особливості впливу роботи автозаправних станцій (АЗС) на довкілля. Розглянуто технологічні особливості роботи АЗС: «мале» дихання, «велике» дихання. Рівні концентрацій і склад речовин: випаровувань газоподібних речовин, при різних експлуатаційних режимах роботи АЗС. Розглянуті методики визначення маси випаровувань різних видів палива: та скрапленого вуглеводневого газу, бензину, дизельного палива.

It was analyzed specific features of the influence from petrol stations on the environment. It was studied technical details of petrol stations operating: «small» breathing and «huge» breathing. Levels of the concentration and structure of the chemical agents: evaporation of gaseous materials in different operating modes of the petrol stations. It was taken a view on methods for determination of the weight of the evaporated types of petrol: liquid gas, gasoline, diesel fuel. It was developed estimated model for spreading area of the evaporations on the base of analyze of the standard petrol station. It was recommended to introduce new source of pollution (emission).
Analytical model of petrol station vapor emissions
Keywords: викиди; розсіювання; джерело; забруднення; "мале" дихання; "велике" дихання; emission; petrol stations; diffusion; source; pollution